judul artikel: OPTIMALISASI ASAS FIKSI HUKUM DALAM PENGATURAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (STUDI DI SINGARAJA, BULELENG) - kadek, wiwin asita; Wirawan, Ketut Adi; Payana, Gede Andra Uky (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
The application of the principle of legal fiction to a regulation causes problems in society, many people do not know the enactment of a regulation due to lack of access to information and socialization from the government and the low quality of human resources who cannot understand the contents of the regulations that have been enacted, so that the regulation does not apply effectively in society and this unconsciously causes many irregularities in its implementation. The problem in this research is the enactment of the principle of legal fiction which causes problems in Buleleng Regency regarding the non-optimal enforcement of local regulations related to the acquisition duty of land and building rights to the community. In this case, the community is disadvantaged due to not knowing the contents of regional regulations, especially in terms of the implementation of the transfer of rights to land certificates through inheritance, so that this is widely utilized by irresponsible individuals, by charging fees that are not in accordance with applicable regulations. This type of research uses empirical legal research. The results of this study are that the Buleleng Regency Regional Regulation Number 1 of 2011 on Fees for Acquisition of Land and Building Rights has not been effectively applied to the people of Buleleng, due to the fact that the public does not know and understand the entire contents of this regulation so that it can be said that the principle of legal fiction applies in the enforcement of this regulation, then many public officials se